Modelos pedagógicos en el subnivel dos de educación inicial en la Unidad Educativa Particular Marista - Muzo Gualoto, Sylvia Johanna (2018)
This case analysis on pedagogical models in initial education is interested in providing current data on the pedagogical model that is being applied in the institutions at the initial level, because it has not been possible to consolidate a pedagogical model for this Level. The research contains a theoretical framework which details information on basic concepts of education, pedagogical models in general, pedagogical models in initial education and pedagogical models of the initial education curriculum 2014. Below are details on the methodology implemented during the investigative process to obtain data on the pedagogical models, which were then analyzed and established relationships of coherence and approximation between them, starting from The revision of the pedagogical model proposed in the Institutional Educational Project (PEI) and the observed in the didactic practice in the Particular educational unit "Marist". Finally, the conclusions are presented based on the objectives that guided this research.